2016
DOI: 10.1098/rstb.2015.0404
|View full text |Cite
|
Sign up to set email alerts
|

Heterotaxy inCaenorhabditis: widespread natural variation in left–right arrangement of the major organs

Abstract: Although the arrangement of internal organs in most metazoans is profoundly left–right (L/R) asymmetric with a predominant handedness, rare individuals show full (mirror-symmetric) or partial (heterotaxy) reversals. While the nematode Caenorhabditis elegans is known for its highly determinate development, including stereotyped L/R organ handedness, we found that L/R asymmetry of the major organs, the gut and gonad, varies among natural isolates of the species in both males and hermaphrodites. In hermaphrodites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…In addition, increased levels of male-male competition in experimental contexts can lead to the evolution of larger male sperm size (LaMunyon and Ward 2002;Palopoli et al 2015), consistent with the relevance of sperm size for male competitive ability. Although self-fertilization is the predominant mode of C. elegans reproduction, with rare occurrence of males and outcrossing events in natural populations (Jovelin et al 2003; Barrière and Félix 2005;Sivasundar and Hey 2005), ample natural variation in diverse male traits exists (Hodgkin and Doniach 1997;Teotónio et al 2006;Palopoli et al 2008Palopoli et al , 2015Morran et al 2009;Anderson et al 2010;Noble et al 2015;Alcorn et al 2016), including male sperm size (Ward and Carrel 1979;LaMunyon and Ward 1995, 1998, 1999Murray et al 2011;Palopoli et al 2015). Moreover, gonochoristic (male-female) Caenorhabditis species exhibit, on average, much larger male sperm than the three androdioecious species, C. briggsae, C. elegans, and C. tropicalis, in which male-male competition is much weaker (LaMunyon and Ward 1999;Vielle et al 2016).…”
mentioning
confidence: 99%
“…In addition, increased levels of male-male competition in experimental contexts can lead to the evolution of larger male sperm size (LaMunyon and Ward 2002;Palopoli et al 2015), consistent with the relevance of sperm size for male competitive ability. Although self-fertilization is the predominant mode of C. elegans reproduction, with rare occurrence of males and outcrossing events in natural populations (Jovelin et al 2003; Barrière and Félix 2005;Sivasundar and Hey 2005), ample natural variation in diverse male traits exists (Hodgkin and Doniach 1997;Teotónio et al 2006;Palopoli et al 2008Palopoli et al , 2015Morran et al 2009;Anderson et al 2010;Noble et al 2015;Alcorn et al 2016), including male sperm size (Ward and Carrel 1979;LaMunyon and Ward 1995, 1998, 1999Murray et al 2011;Palopoli et al 2015). Moreover, gonochoristic (male-female) Caenorhabditis species exhibit, on average, much larger male sperm than the three androdioecious species, C. briggsae, C. elegans, and C. tropicalis, in which male-male competition is much weaker (LaMunyon and Ward 1999;Vielle et al 2016).…”
mentioning
confidence: 99%
“…Most of our understanding of C. elegans biology is based on studies on a single genetic background, that of the laboratory reference strain N2. The identification of wild C. elegans isolates bearing distinct haplotypes has uncovered considerable phenotypic variation and developmental plasticity in this species (Hodgkin and Doniach, 1997;Harvey et al, 2008;Milloz et al, 2008;Andersen et al, 2012;Alcorn et al, 2016;Cook et al, 2016;Greene et al, 2016;Frézal et al, 2018;Gimond et al, 2019;Lee et al, 2019). Knocking down essential genes in the wild strains yielded distinct phenotypes and has uncovered substantial cryptic variation between the spectrum of isotypes (Paaby et al, 2015;Torres Cleuren et al, 2019).…”
Section: Rapid Developmental System Drift Among C Elegans Wild Isolatesmentioning
confidence: 99%
“…Genetic analysis of heterotaxy is also being conducted by Alcorn et al [41], who use C. elegans in their search for disease loci. The commonly used laboratory strain of this nematode exhibits a stereotypical gut-gonad L/R asymmetry that has been shown to be established during early embryogenesis, i.e.…”
Section: Synopsis Of Laterality Chaptersmentioning
confidence: 99%
“…during the division of the two anterior granddaughter cells of four-cell stage embryo. In examining nearly 100 evolutionarily diverged isolates of this species, Alcorn et al [41] discovered that there is naturally existing variation in L/R organ asymmetry, and moreover, that some species exhibit heterotaxy in up to 11-12% of the animals. By conducting genetic crosses of lines showing normal L/R situs with lines showing heterotaxy, these investigators found that heterotaxy is associated with three genomic regions.…”
Section: Synopsis Of Laterality Chaptersmentioning
confidence: 99%